Implementation and outcomes of a patient tracing programme for HIV in Trinidad and Tobago. Issue 11 (2nd November 2019) - Jeffrey Edwards, R.; Lyons, Nyla; Bhatt, Chintan; Samaroo-Francis, W; Hinds, Avery; Cyrus, Elena
ABSTRACT: A patient tracing programme was implemented at an HIV clinic in Trinidad and Tobago to address the problem of defaulters from HIV care and non-adherence to antiretroviral treatment (ART). The study objective was to evaluate the implementation and outcomes of this programme conducted between April and September 2017. Using patient tracing contact methods, trained social workers attempted to contact 1058 patients lost to follow up (LTFU) between July 2016 and March 2017. Of the 1058 LTFU, 192 were ineligible: 27 (2.5%) were transferred to another clinic, 64 (6%) deceased, 35 (3.3%) hospitalised, 50 (4.7%) migrated and 16 (1.5%) incarcerated. Of the 866 eligible patients for patient tracing, 277 (32%) remained permanently LTFU and 589 (68%) were successfully contacted, re-engaged in care and received adherence counselling. Of the 589 who returned to care, 507 (86%) restarted ART. The three most common barriers reported among the 589 who were reengaged were 'forgetting their appointments' (20%), 'being too busy/work' (16%), and 'not wanting to be seen attending the HIV clinic' (12%). The study findings demonstrated the tracing programme as feasible for re-engaging those who are LTFU and highlighted barriers that can be addressed to further improve retention in HIV care among people living with HIV.